Assesment of lineal versus landmarks- based morphometry for discriminating species of Mugilidae (Actinopterygii) - González Castro, Mariano (2012)
Meristic and different morphometric approaches were employed to assess the discrimination of 7 species of Mugilidae fishes (Mugil cephalus, M. liza, M. curema, M. hospes, Liza aurata, L. ramada, and Chelon labrosus), but also to contribute to a better understanding of body-shape differences among this valuable species group. Three types of variables and their corresponding morphometric approaches were employed: 1) linear morphometrics measurements (LMMs); 2) interlandmark distances (IlDs); and 3) coordinate data (landmarks). Before the analyses, data exhibiting allometric growth were normalized. Data analysis included a one-way ANOVA (meristic data), a principal component analysis (PCA), and a cross-validated discriminant analysis (DA). The ANOVA showed significant differences in both lateral and transverse series scales. The PCA based on LMMs allowed the characterization of 6 groups, although some overlap between them was detected. The DA correctly classified 68.4% of the fishes according to their LMMs. The centroids of the 8 groups were separated for both the 1st and 2nd discriminant functions. The morphometric analysis based on IlDs yielded the best discrimination rates of the 3 approaches employed (96% for the DA). In the geometric morphometric analysis, the DA correctly classified 83.8% of the fishes according to their body shape. Although 8 groups were defined, some overlap among samples was detected. Mugil hospes was the best defined and most isolated species as observed in both the PCA and DA. Interestingly, the 3 morphometrics approaches employed separated M. curema specimens in 2 groups (Argentinean and Mexican samples). Moreover, European and Mexican samples of M. cephalus plotted separately in the PCA of the LMM- and IlD-based approaches. These shape differences among M. curema of Argentina/Mexico and M. cephalus of Europe/Mexico reinforce the current hypothesis of a species complex, or even undescribed species as previously suggested by the authors.